KERTAS INDIKATOR ASAM BASA DARI EKSTRAK ETANOL RIMPANG TANAMAN TEMULAWAK (Curcuma xanthorrhiza Roxb.) - Sumiati Sumiati (UIN Sunan Kalijaga Yogyakarta, 2019)
Temulawak is a type of plants which has a height of up to 2 meters. Curcumin content in temulawak plants is widely used as an anti-tumor, antioxidant, malaria drug, preventing the transmission of HIV in humans, material for making traditional herbal medicine and as a natural coloring agent in food processing. The purpose of this study was to determine whether temulawak rhizome extract can be used as an indicator of acid base. The extraction of ginger rhizome plants was carried out by maceration method using ethanol solvent with immersion time of 60 minutes, 120 minutes and 180 minutes. The results of the extraction of ginger rhizome plants then measured their absorbance values using UV-Vis spectrophotometer at a wavelength of 424 nm to determine the best soaking time. Temulawak rhizome extract which has the highest absorbance value is used to make indicator paper by immersing rough filter paper in temulawak plant rhizome extract and then indicator paper is dried at room temperature. The indicator paper is tested for color changes in pH 1-13 solutions. Based on the results of the study showed that temulawak rhizome extract can be used as an indicator of acid base with the best soaking time of 180 minutes and the color change of the pH 8-13 route under strong weak base bases.